The Influence of Peer Tutoring Method to the English Learning Outcomes - ARSYAD, Hasmita Dewi Eliyanti; SUHARTINA, Suhartina; ASTRI, Zul (Politeknik Negeri Ujung Pandang, 2023)
Peer tutoring has become an increasingly popular as a method in recent years. This study aimed to determine the influence of the peer tutoring method on the student learning outcomes in English class VII grade students of SMP Negeri 5 Mandai. This type of research is experimental research. The data collection technique was done by using test and documentation techniques. Data collection tool in the form of multiple-choice questions that have previously been tested is analyzed with validity and reliability data analysis techniques in the form of quantitative. The results showed that the average value of control class post-test was 6.422 while the average value of experimental class 14.831. Based on the results of calculating of the hypothesis test shows the value of sig (2-tailed) 0.05, (0.116 < 0.05), H0 is rejected